Pertumbuhan Mangrove Rhizophora apiculata pada Pembibitan Mangrove di Kelompok Segara Ayu, Kedonganan, Bali - Hamdan Hamdan; Ni Made Ernawati; Ayu Putu Wiweka Krisna Dewi (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This research aims to determine the growth of Rhizophora apiculata mangroves based on height, number of leaves and stem diameter in mangrove nurseries in the Segara Ayu Group, Kedonganan, Bali. The research was conducted for six months, from March to August 2025, using quantitative descriptive methods. Observations were made on 40 plants spread across four demonstration plots, with data collected every two weeks. The environmental parameters measured include temperature and salinity. The results showed that the absolute growth in plant height ranged between 27–31 cm, with relative growth of 27.4–33.7%. The average number of leaves reaches 11 to 18 pieces, while the stem diameter ranges from 1.7–2.7 cm. Environmental conditions at the research location are classified as supporting optimal growth, with salinity of 24–28 ppt and temperature of 28–31°C, In general, Rhizophora apiculata plants show good growth during the nursery period, which indicates that the Segara Ayu location has ecological conditions that are suitable for mangrove rehabilitation activities.